TEACHER UNDERSTANDING IN DATA COLLECTION TECHNIQUES FOR UPPER CLASS COUNSELING AT SDN 2 TAKERANKLATING - Aisa putri rahmawati; Siti khusnul khotimah; Arfian Mudayan (Universitas Muhammadiyah Lamongan, 2024)
Analysis of teacher understanding in collecting guidance and counseling data in elementary schools is very important for teachers to know the character and needs of students. This research aims to determine teachers' understanding of high-class counseling guidance data collection techniques at SDN 2 Takeranklating. The research method uses descriptive qualitative methods. The subject of this research was the 5th grade teacher at SDN 2 Takeranklating. The instruments used were interviews and observations. The results of this research are (1) upper class teachers understand guidance and counseling data collection techniques, (2) the data collection technique used is non-cognitive diagnostic assessment, (3) teachers get data from various sources, (4) teachers have not carried out tests for data retrieval . Suggestions for future researchers are that the research object is expected to be expanded and not limited to just one source.